2018
DOI: 10.1093/ecco-jcc/jjx185
|View full text |Cite
|
Sign up to set email alerts
|

CD16+ Macrophages Mediate Fibrosis in Inflammatory Bowel Disease

Abstract: Our study demonstrates that STAT6 deficiency dysregulates the macrophage response to inflammatory outbursts by increasing the presence of a population of CD16+ macrophages that seems to contribute to intestinal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…It seems likely that these differences, rather than cause, are consequence of the different extent of fibrosis, which in turn depends on the presence of sucnr1 in those cells of the transplanted tissue mediating the fibrotic response. Of interest, graphs from both groups showed an increased expression of CD16, a recently reported marker of pro-fibrotic macrophages, 28 and of the well-known fibrogenic mediator, TGFβ. 1 The presence of similar levels of these pro-fibrotic elements in both, WT and Sucnr1 −/− mice suggest that fibrosis, in the heterotopic transplant model, may depend mainly on the pro-inflammatory cytokines, although, a reduced cellular reactivity to fibrogenesis resulting from the lack of Sucnr1 in intestinal tissue cannot be ruled out.…”
Section: Discussionmentioning
confidence: 85%
“…It seems likely that these differences, rather than cause, are consequence of the different extent of fibrosis, which in turn depends on the presence of sucnr1 in those cells of the transplanted tissue mediating the fibrotic response. Of interest, graphs from both groups showed an increased expression of CD16, a recently reported marker of pro-fibrotic macrophages, 28 and of the well-known fibrogenic mediator, TGFβ. 1 The presence of similar levels of these pro-fibrotic elements in both, WT and Sucnr1 −/− mice suggest that fibrosis, in the heterotopic transplant model, may depend mainly on the pro-inflammatory cytokines, although, a reduced cellular reactivity to fibrogenesis resulting from the lack of Sucnr1 in intestinal tissue cannot be ruled out.…”
Section: Discussionmentioning
confidence: 85%
“…More precisely, the number of intestinal IL-36α + Mfs increase in the colon of Crohn's patients with stenosis (298). Functionally, IL-36 acted directly on human mesenchymal cells to elicit a profibrotic transcriptional program (298), suggesting that the increase of IL-36α + Mfs could induce intestinal fibrosis during chronic inflammation in IBD patients (298)(299)(300). Corroborating this, Martin et al recently showed in situ that immature Mfs were always in the close vicinity of activated fibroblasts in intestinal mucosa of Crohn's patients (263).…”
Section: Function Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
“…For instance, the compartment of myeloid mononuclear cells including dendritic cells [DCs] and macrophages has not been characterised in detail. Effects of macrophages on intestinal fibrosis have been demonstrated, 65,66 and our results do not exclude a modulation of frequency, activation level, and/ or phenotype of macrophages or DCs, which remains a limitation of our study.…”
Section: Discussionmentioning
confidence: 55%